2022
DOI: 10.3389/fpubh.2022.836898
|View full text |Cite
|
Sign up to set email alerts
|

A Prospectively Validated Nomogram for Predicting the Risk of PHQ-9 Score ≥15 in Patients With Erectile Dysfunction: A Multi-Center Study

Abstract: BackgroundAlthough erectile dysfunction (ED) often occurs simultaneously with depression, not all patients with ED suffer major depression (MD), with a PHQ-9 score ≥15 indicating MD. Because the PHQ-9 questionnaire includes phrases such as “I think I am a loser” and “I want to commit suicide,” the psychological burdens of ED patients are likely to increase inevitably after using the PHQ-9, which, in turn, may affect ED therapeutic effects. Accordingly, we endeavored to develop a nomogram to predict individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“… 4 Male sexual function can be assessed by several psychometric scales: the 6-item International Index for Erectile Function (IIEF-6), the Erection Hardness Scale (EHS), and the Masturbation Erection Index (MEI) can be used to assess aspects related to erectile function; moreover, the Premature Ejaculation Diagnostic Tool (PEDT) can be used to assess the presence of premature ejaculation (PE) and its clinical consequences. 5 6 7 8 9 10 Several studies have confirmed the diagnostic accuracy of the EHS and IIEF-6. 11 12 13 14 15 The MEI is an adaptation of the IIEF-6 that is applied to masturbation; this scale is particularly useful for erectile dysfunction (ED) patients who have not engaged in penetrative sexual intercourse in the past 4 weeks.…”
Section: Introductionmentioning
confidence: 92%
“… 4 Male sexual function can be assessed by several psychometric scales: the 6-item International Index for Erectile Function (IIEF-6), the Erection Hardness Scale (EHS), and the Masturbation Erection Index (MEI) can be used to assess aspects related to erectile function; moreover, the Premature Ejaculation Diagnostic Tool (PEDT) can be used to assess the presence of premature ejaculation (PE) and its clinical consequences. 5 6 7 8 9 10 Several studies have confirmed the diagnostic accuracy of the EHS and IIEF-6. 11 12 13 14 15 The MEI is an adaptation of the IIEF-6 that is applied to masturbation; this scale is particularly useful for erectile dysfunction (ED) patients who have not engaged in penetrative sexual intercourse in the past 4 weeks.…”
Section: Introductionmentioning
confidence: 92%